2012
DOI: 10.7326/0003-4819-156-10-201205150-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Care Management Program to Prevent Chronic Obstructive Pulmonary Disease Hospitalizations

Abstract: A CCMP in patients with severe COPD had not decreased COPD-related hospitalizations when the trial was stopped prematurely. The CCMP was associated with unanticipated excess mortality, results that differ markedly from similar previous trials. A data monitoring committee should be considered in the design of clinical trials involving behavioral interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(238 citation statements)
references
References 38 publications
6
221
3
8
Order By: Relevance
“…37 Not all interventions based on self-management education have yielded positive outcomes. 30,38 In addition, it isn't yet clear why such interventions fail when they do, or whether social determinants of health are more important than diagnostic considerations in some clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…37 Not all interventions based on self-management education have yielded positive outcomes. 30,38 In addition, it isn't yet clear why such interventions fail when they do, or whether social determinants of health are more important than diagnostic considerations in some clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education accompanied by instruction for self-management and individualized, written action plans can improve the outcome of exacerbations [48]. Although there are studies that show a beneficial effect of disease self-management in COPD [48], a study with negative results concerning patient’s self-management and COPD-related hospitalizations was recently published [49]. Quality assessment in patient instruction and survey by specially trained medical staff is therefore crucial.…”
Section: Management Of Copdmentioning
confidence: 99%
“…In COPD, this approach has in some studies resulted in reduced healthcare costs [68], a lower rate of hospitalization due to COPD exacerbations as well as for other reasons [69]. In contrast, other well-designed studies have found excess mortality in self-help plan groups [70] and no effect of nurse-controlled interventions [71]. These contradictory results illustrate the complexity of severe chronic lung disease and highlight the need for personalized management.…”
Section: Overall Approachmentioning
confidence: 99%